U‐Pb Geochronology of Paleosol Carbonate Cements by LA‐ICP‐MS: A Proof of Concept and Strategy for Dating the Terrestrial Record - L. E. Aguirre Palafox; A. Möller; N. M. McLean; G. A. Ludvigson; C. E. Colombi; I. P. Montañez (Geochemistry, Geophysics, Geosystems, 2024)
Abstract This study investigates the potential of laser ablation inductively coupled plasma mass spectrometry (LA‐ICP‐MS) U‐Pb dating for carbonate nodules in the Late Triassic Ischigualasto Formation of northwestern Argentina. We establish a fully characterized paragenetic sequence to guide the analysis of three pedogenic carbonates and compare the U‐Pb ages with published geochronology from volcanic ashes within the sedimentary succession. Our findings demonstrate the importance of interpreting U‐Pb data within a well‐defined paragenetic framework for accurate age interpretation of pedogenic carbonates. We observe variations in U‐Pb isotopic signatures across different generations of carbonate precipitates and identify syn‐pedogenic and early burial calcite cements as most suitable for precise dating. Respectively, these two calcite cements are interpreted as microcodium and crack‐lining calcite cements formed early in the paragenetic sequence during pedogenesis to early burial of the paleosols as they transitioned from the unsaturated vadose to saturated phreatic zone below the water table. The U‐Pb ages obtained from the carbonate nodules agree with the radioisotopic ages of volcanic ashes, supporting the validity of our dating strategy. These results contribute to advancing U‐Pb carbonate geochronology and highlight its increased potential for dating sedimentary records in the terrestrial realm. Future research should focus on replicating similar work on different carbonate nodules within the Ischigualasto Fm and expanding the application of LA‐ICP‐MS U‐Pb dating to other carbonate‐bearing formations, especially in successions with limited absolute ages or where volcanic ashes are sparse or absent.